2021
DOI: 10.3390/su13031415
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Effects of Eco-Driving on Courier Delivery

Abstract: In recent years, eco-driving has proven to be an effective tool for reducing fuel consumption and greenhouse gas (GHG) emissions. Until now, most research carried out has focused on ordinary drivers applying eco-driving techniques on their usual routes. However, there is little research on professional driver couriers. This research is aimed at analyzing the effects that eco-driving has on fuel consumption and GHG emissions on courier deliveries in small cities such as Caceres (Spain). For this purpose, a real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
1
8
0
1
Order By: Relevance
“…For example, Díaz-Ramirez et al [ 27 ] found that more experienced drivers are not likely to change their behaviour after receiving eco-driving guidance, while other socio-demographic characteristics (such as age and education levels) are not significant. Similar results can also be found in [ 26 , 33 , 80 ].…”
Section: Designs Of Eco-driving Guidancesupporting
confidence: 90%
“…For example, Díaz-Ramirez et al [ 27 ] found that more experienced drivers are not likely to change their behaviour after receiving eco-driving guidance, while other socio-demographic characteristics (such as age and education levels) are not significant. Similar results can also be found in [ 26 , 33 , 80 ].…”
Section: Designs Of Eco-driving Guidancesupporting
confidence: 90%
“…Wu et al [ 101 ] measured the effectiveness of eco-driving training for both professional and non-professional drivers and they found that non-professional drivers showed a greater willingness to improve their behavior than professional drivers and the former had a more obvious improvement in fuel saving. Coloma et al [ 102 ] studied the impact of eco-driving training on postal-truck drivers and got a similar conclusion. In fact, the essential difference between professional and non-professional drivers is the number of driving years and driving experience; thus, the reason for this difference may be related to the rich driving experience and long-term habits of professional drivers.…”
Section: Eco-driving Applicationmentioning
confidence: 73%
“…However, in terms of the impact of road traffic environment on the effect of eco-driving training, different scholars have reached different conclusions. Some scholars believe that driving on unobstructed roads is more conducive to the implementation of eco-driving strategies, so the fuel-saving effect is more obvious [ 102 , 109 ]. Coloma et al [ 102 ] pointed out that eco-driving training seems to be more effective in small but not crowded cities.…”
Section: Eco-driving Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, short-term research and efforts must focus on leveraging and finding new opportunities for improving efficiency in urban freight transport, in terms of both optimization and innovation. Among these, one of the main options to optimize traditional strategies (i.e., LMD carried out by Light Duty Vehicles-LDVs) is to improve route planning skills since it has been demonstrated that proper route planning can save up to 20% of fuel consumption and reduce the corresponding emissions [10][11][12].…”
Section: Introductionmentioning
confidence: 99%